Social Media Use in European Hotels: Benefits and Main Challenges - Aurora Garrido-Moreno; Nigel Lockett (Tourism & Management Studies)
The advent of Social Media tools has been one of the most relevant technological innovations in recent years and has strongly impacted the tourism industry. Despite the numerous benefits that Social Media can offer to hotels, transforming the way they relate to customers and opening a vast array of new possibilities, its implementation implies also numerous challenges. Considering that the use of Social Media is becoming increasingly popular, it seems to be critical to understand how hotels can use them strategically to reinvent customer relationships. This study explores the topic following a mixed methodology, combining both quantitative and qualitative data from a European sample of 312 hotels. Results suggest that review sites and social networks were the most used tools. The main advantag